KONTRIBUSI POWER OTOT LENGAN DAN BAHU TERHADAP HASIL LEMPAR LEMBING PADA SISWA KELAS X SMK MIGAS INOVASI RIAU - Munawir '; Saripin '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the result of observation of the students of class X of SMK Migas Inovasi Riau, there are phenomena that happened like there are still many students who have not mastered the basic technique of javelin throwing correctly. Some students still look rigid movement during javelin throwing. Judging from the distance javelin throw is still less satisfactory or too close, this is due to physical conditions such as strength and explosive muscle power that has not been trained. This study aims to determine whether there is Contribution of Arm Muscle Power and Shoulder To The Result Of Javelin Throw On Student Putera Class X SMK Migas Inovasi Riau. The form of this research is correlation research. The sample in this research is Student of Putera Kelas X SMK Migas Inovasi Riau totaling 20 people. From the calculation of the analysis of the calculation of correlation "r" on product moment (rxy) obtained rhitung = 0.479. This means that there is a relationship between arm and shoulder muscle power with javelin throwing ability with the result of javelin throwing with the contribution value of 22.94% in students of Putra Class X SMK Migas Inovasi Riau. This means that the power role of arm and shoulder muscles is quite dominant in producing javelin throw and 77.06% influenced by other physical condition factorsKeywords: Power Arm Sleeves and Shoulder and Lempar Lembing